Intrinsic Motivation Dan Performance : Studi Meta Analisis - Bagus Riyono (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2008)
Intrinsic motivation as a theory emerged in a study that defies the effect of reward to performance. This claim was strongly opposed by behaviorists, who believed that the role of rewards as reinforcement was very important. This controversy continues until today. Since then, there had been competing researches guided by two different perspectives.This study examines the relationship between intrinsic motivation and performance through meta-analysis techniques. 24 studies were selected according to the inclusion criteria of this study, and analyzed to find the correlation of intrinsic motivation and performance. The result show that correlation between intrinsic motivation and performance is r = 0.26. This result could lead to two conclusions. The first conclusion could be that there is a significant correlation between intrinsic motivation and performance. On the other hand the correlation was not as strong as expected, meaning that external factors, like reward, could have stronger correlation with performance. Key words : meta-analysis, intrinsic motivation, performance